Assessment of Ticagrelor Versus Clopidogrel Treatment in Patients With ST-elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. Issue 2 (August 2016) - Tang, Xiuying; Li, Runjun; Jing, Quanmin; Wang, Qingsheng; Liu, Peng; Zhang, Peidong; Liu, Yingfeng
Abstract : Aims: Ticagrelor improves the clinical outcomes in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). However, few studies have directly compared the efficacy and safety of ticagrelor against clopidogrel, an oral, thienopyridine-class antiplatelet drug. This study compared the efficacy and safety of ticagrelor and clopidogrel in patients with STEMI undergoing PPCI. Methods: We enrolled 400 patients with STEMI undergoing PPCI at the Zhujiang Hospital of Southern Medical University and the First Hospital of Qinhuangdao, China, between January 01, 2013 and April 30, 2015. All patients received 300 mg of aspirin and were randomized to receive one of the following treatments: (1) a loading dose of clopidogrel (600 mg) before PPCI followed by clopidogrel (75 mg once daily for 1 year) post PPCI or (2) a loading dose of ticagrelor (180 mg) before PPCI followed by ticagrelor (90 mg twice daily for 1 year) post PPCI. Some patients were treated by intracoronary bolus of a glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitor [tirofiban (10 μg/kg) plus maintenance infusion (0.15 μg −1 ·kg·min −1 ) for 24–36 hours] in accordance with specified guidelines. The primary end points evaluated were major adverse cardiovascular and cerebrovascular event (MACCE) [defined as a composite of overall death, myocardial infarction (MI), unplanned revascularization, or stroke], stent thrombosis, and the composite end point of CV death, nonfatal MI, and stroke. The supplemental use of GPIIb/IIIa inhibitors in the clopidogrel and ticagrelor groups was monitored as another study end point, although the secondary safety end point evaluated was the incidence of bleeding events. Results: Compared with the clopidogrel-treated group, ticagrelor treatment significantly reduced the incidence of MACCE [5 vs. 14; odds ratio (OR), 0.341; 95% confidence interval (CI), 0.120–0.964; P = 0.034] and the composite end points of cardiovascular death, nonfatal MI, and stroke (4 vs. 13; OR, 0.294; 95% CI, 0.094–0.916; P = 0.026). Fewer patients in the ticagrelor group received GPIIb/IIIa inhibitors after PPCI compared with those in the clopidogrel group (10 vs. 21; OR, 0.449; 95% CI, 0.206–0.979; P = 0.040). However, there were no significant differences between the groups in the incidences of all-cause mortality, nonfatal MI, unplanned revascularization, stroke, stent thrombosis ( P = 0.522, P = 0.246, P = 0.246, P = 0.217, P = 0.246, respectively), or bleeding events (10 vs. 7; OR, 1.451; 95% CI, 0.541–3.891; P = 0.457). Conclusions: Among patients with STEMI undergoing PPCI, ticagrelor reduces the incidence of MACCE and the composite end point of cardiovascular death, nonfatal MI, and stroke compared with clopidogrel. Ticagrelor also reduces the need for GPIIb/IIIa inhibitors. However, no significant difference was observed in the risk of bleeding between the 2 groups.